(untitled) (Baltic Journal of Real Estate Economics and Construction Management, 2013)
The article investigates approaches to improve the management of residential real estate in today's Russia. The activities of urban enterprises of Russia remain inefficient and costly. It shows the changes in the legislative and regulatory framework for the activities of management companies in the field of public utilities. The experience of several European countries on the use of mechanisms for public-private partnerships, outsourcing and information in the urban economy are depicted. The reasons why the experience gained in Europe, effective management of residential real estate is slowly being implemented in Russia are also highlighted in the article.